Discursive Hegemonic Mediation dalam dalam Pemberitaan Media tentang Just Energy Transition Partnership (JETP) di Indonesia: Analisis Wacana Kritis Model Fairclough - Robertua, Verdinand; Oktavian, Riskey; Gadaza, Aniza C; Margaretha, Ruth (Universitas Komputer Indonesia, 2025)
The Just Energy Transition Partnership (JETP), promoted by the Group of Seven (G7), is framed as a climate finance initiative that links energy transition with social justice in developing countries. In Indonesia, however, JETP operates not merely as a technical policy scheme but as a discursive arena where donor-country hegemony is articulated and stabilized. This study applies Discursive Hegemonic Mediation (DHM) to examine how global dominance is reproduced through the normalization of dependency and the limitation of critical perspectives within policy narratives. Methodologically, it employs Critical Discourse Analysis (CDA), drawing on Norman Fairclough’s three-dimensional model to analyze the relationship between media texts, discursive practices, and broader political-economic structures. Findings from national online media coverage reveal an ambivalent framing of JETP: while narratives of green investment opportunities and transition urgency are amplified, structural critiques such as the predominance of loans over grants and uncertainties in donor commitments are reduced to technical concerns. Consequently, the media act as hegemonic mediators, permitting limited criticism without challenging the broader power relations of. The study concludes that JETP’s legitimacy in Indonesia is discursively constructed through processes that normalize dependency within the energy transition agenda. Keywords— Discursive Hegemonic Mediation, Global Climate Finance, Just Energy Transition Partnership (JETP), Just Energy Transition Partnership